Semantic categories of social actors in MH17 disaster - Shamsudin, Sarimah; Wan Md Adnan, Wan Najmiyyah (Opción, 2019)
The main objective of this paper is to identify the semantic categories of social actors in the news discourse of the MH17 disaster. The methodology used for this paper is a corpus analysis in which we identify the most frequent and salient words using corpus analysis software. Results show that social actors in MH17 disaster news articles can be categorized into three main groups: authority and decision-makers, responsible parties and disaster victims. In conclusion, social actors can be represented based on socially grouped together words either to indicate togetherness or sharing similarities.